2018
DOI: 10.1142/s0219877018500128
|View full text |Cite
|
Sign up to set email alerts
|

Lean Startup Method Hampers Breakthrough Innovations and Company's Innovativeness

Abstract: The Lean Startup Method (LSM) provides a systematic management of innovation processes within startups and even within well-established companies. Despite its wide use by a lot of innovative companies, this study claims that using the LSM compromises the development of breakthrough and radical innovations and also companies' innovativeness is hindered given that companies usually follow the method and its principles blindly, without fully understanding its advantages and disadvantages. The aim of this study is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…At last, Yordanova (2018) argues that LS and the principle of user involvement hinder the development of breakthrough innovation. Additionally, the author states that companies tend to adopt the methodology blindly without fully understanding its advantages and disadvantages.…”
Section: Thematic Analysismentioning
confidence: 99%
“…At last, Yordanova (2018) argues that LS and the principle of user involvement hinder the development of breakthrough innovation. Additionally, the author states that companies tend to adopt the methodology blindly without fully understanding its advantages and disadvantages.…”
Section: Thematic Analysismentioning
confidence: 99%
“…The author will also validate the concept by conducting a research focusing on the negative effects possible from using such model for business organizations as some research on related topics indicates that it may exists. A concrete example of such a research is on using Lean start-ups and how that may hamper breakthrough innovations and company's innovativeness (Yordanova, 2018b).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In the process of undertaking this study, we found scope for further research: Type of innovation : The literature shows that the innovation adopted by Start-ups could be Breakthrough (Yordanova, 2018), Radical (McDermott, 2002), Disruptive (Christensen et al, 2015), Sustaining or Incremental (Hossain & Kauranen, 2016). Based on empirical observations, it would be interesting to identify the type of innovation adopted by these ISs.…”
Section: Scope For Further Researchmentioning
confidence: 99%